MODIFICATION OF NANOSTRUCTURE IN CARBON-DOPED ZNO: ELECTRICAL AND OPTICAL PROPERTIES SYNTHESIZED VIA SPUTTERING AND PYROLYSIS OF ZN-MOF DERIVATIVES - Novi Hendri, Yasni
Zinc oxide (ZnO) is a semiconductor with a wide band gap of 3.33-3.37 eV and exceptional optical properties within the UV region. Introducing carbon doping to ZnO has the potential to reduce the band gap energy, resulting in broader optical absorption and thus serving as an alternative to enhance device performance. This study involved the preparation of carbondoped ZnO using sputtering and pyrolysis methods to modify surface structures and investigate their effects on electrical and optical properties. Density functional theory (DFT) was employed to support the experimental findings. In the sputtering method, samples are obtained in the form of thin films where ZnO and carbon-doped ZnO (ZnO:C-1, ZnO:C-2) grow on a Silicon (100) substrate with optimized deposition parameters (Power= 12W, growth temperature =300 ?, time= 4 hours, pressure = 0.3 kPa). Heating treatment after deposition (thermal annealing) was applied to the ZnO thin film at a temperature of 600 ? (ZnO/ann600) and 800 ? (ZnO/ann-800) under oxygen gas flow for 10 minutes. Furthermore, using the pyrolysis method, powdered samples were obtained, where Zn-MOF was converted into ZnO/C after heating at a temperature of 450 ? for 2 hours in various atmospheric conditions: nitrogen, oxygen, and air (ZnO/C-O2, ZnO/C-N2, ZnO/C-air). This research involved photocatalytic tests with the aim of evaluating the degradation capability of Rhodamine-B pollutant at a concentration of 20 ppm. Photocatalytic testing of ZnO/C samples derived from Zn-MOF was carried out using a portable solar simulator PEC-L01 (1000 W/m2 ). ZnO thin films grown using the sputtering method produce cone-shaped nanocolumnar structures (ZnO height= 850 nm) and change significantly into rods after annealing at temperatures of 600 ? (ZnO/ann-600 height=600 nm) and 800 ? (ZnO/ann- height 800=300 nm). Thermal annealing treatment induces an increase in the lattice constant c from 5.224 Å (ZnO) to 5.226 Å (ZnO/ann-600). Furthermore, we found an elliptical polarization response without saturation, indicating the presence of dominant leakage current and oxygen vacancies in the sample. The highest polarization is found in ZnO/ann-600 (|+Pr/-Pr|= 2.06) which is associated with an increase in the lattice constant c. Besides, ferroelectric characteristics were observed in ZnO/ann-800, with a lower polarization response (|+Pr/-Pr|= 1.14) due to the high density of nanocolumnar rods formed in the sample. Carbon-doped ZnO thin films grown using the sputtering method can reduce the height of ZnO nanocolumnar cones from 850 nm to 800 nm at a C concentration of 12.43% (ZnO:C-1) and 300 nm at a C concentration of 31.76% (ZnO:C -2). Carbon doping on nanocolumnar ZnO can effectively increase the lattice strain (????????????????= 1.658×10-4 , ????????????????:?????1= 5.995×10-4 and ????????????????:?????2= 7.249×10-3 ). The P–E hysteresis loop shows that ZnO:C-1 has the highest coercivity (11.1 kV/cm) which comes from Zn vacancies, while ZnO:C-2 has remanent polarization (4.7 ?C/cm2 ) which comes from oxygen vacancies produces ferroelectric material. Carbon doping reduces the band gap of ZnO from 3.28 eV to 3.25 eV (ZnO:C-1) and 3.23 eV (ZnO:C-2). Density functional theory calculations show that C doping changes the energy band structure in the Fermi energy region due to the contribution of the 2p orbital C atom. The pyrolysis method of Zn-MOF converted into ZnO/C produces various morphological forms depending on the variation of gas applied during pyrolysis. The morphology of Zn-MOF with a rod shape changes to granular (ZnO/C?O2) and spherical (ZnO/C?air) while ZnO/C-N2 still maintains a rod shape. The carbon atom concentration of Zn-MOF changed significantly from 57.43% to 68.41% (ZnO/C?N2), 62.56% (ZnO/C?O2), and 27.7% (ZnO/C?air ). The diffraction peak of ZnO/C?O2 shows the highest crystallinity compared to ZnO/C?air and ZnO/C-N2 where the dominant peak grows in the (101) direction. Furthermore, the BET-specific surface areas obtained were 16.8, 6.81, 12.15, 29.26 m2 /g for the Zn-MOF, ZnO/C?N2, ZnO/C?O2, and ZnO/C-air samples, respectively. ZnO/C?air shows optimal stability performance with a degradation efficiency of up to 94.1% against Rhodamine-B. This research has the potential to provide stable photocatalytic for wastewater purification, especially in the decomposition of Rhodamine-B pollutants. In addition, the results of this research also open up opportunities to obtain multifunctional devices with higher sensitivity and accuracy. Multifunctional devices apply the principles of coupling and integration between the resulting electrical and optical properties. It can also contribute to understanding carbon-doped ZnO materials through method comparisons, thermal annealing treatment, carbon doping, and converting Zn-MOF materials into ZnO/C.